2015
DOI: 10.1158/1055-9965.epi-15-0787
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Risk in Relation to Ambient Air Pollution Exposure at Residences in the Sister Study Cohort

Abstract: Background Some but not all past studies reported associations between components of air pollution and breast cancer, namely fine particulate matter ≤ 2.5 μm (PM2.5) and nitrogen dioxide (NO2). It is yet unclear whether risks differ according to estrogen receptor (ER) and progesterone receptor (PR) status. Methods This analysis includes 47,591 women from the Sister Study cohort enrolled from August 2003-July 2009, in whom 1,749 invasive breast cancer cases arose from enrollment to January 2013. Using Cox pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
82
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(96 citation statements)
references
References 8 publications
(16 reference statements)
9
82
2
1
Order By: Relevance
“…We found moderately stronger associations in pre-than in postmenopausal women, in agreement with two studies (2,3). We present novel findings of enhanced association between PM 2.5 Ours and most other recent studies (2-5) examined air pollution exposure during adulthood, relatively close to breast cancer onset, which may not be the relevant exposure window for the development of breast cancer.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found moderately stronger associations in pre-than in postmenopausal women, in agreement with two studies (2,3). We present novel findings of enhanced association between PM 2.5 Ours and most other recent studies (2-5) examined air pollution exposure during adulthood, relatively close to breast cancer onset, which may not be the relevant exposure window for the development of breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…We found no association between long-term exposure to air pollution and breast cancer incidence in DNC in agreement with other cohort (2,3,5), and in contrast to a case-control study (2). We found moderately stronger associations in pre-than in postmenopausal women, in agreement with two studies (2,3).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Case-control studies of nitrogen dioxide (NO 2 ) (Crouse et al, 2010; Hystad et al, 2015) have reported positive associations, while prospective cohort studies (Andersen et al, 2016; Reding et al, 2015) have reported null or weak positive associations. For instance, a Canadian case-control study reported an odds ratio (OR) of 1.31 (95% confidence interval (CI): 1.00, 1.71) for every 5 ppb increase in NO 2 (Crouse et al, 2010), while a study examining the association between breast cancer risk and air pollution at the enrollment residence of Sister Study cohort participants did not find an overall increase in breast cancer risk, however, a modest positive association was observed between NO 2 exposure and estrogen/progesterone receptor positive breast cancer (risk ratio = 1.10, 95% CI: 1.02,1.19 for an interquartile range difference of 5.8 parts per billion) (Reding et al, 2015). Only one study, a US-based case-control study, evaluated the association between breast cancer and long-term vehicular traffic-related PAH exposure, reporting an OR of 1.44 (95% CI: 0.78, 2.68) for the top 5% level of exposure as compared to below the median (Mordukhovich et al, 2016).…”
Section: Introductionmentioning
confidence: 99%